Adoption of Ultrasound-guided Polymer Nanocarriers in Tumor Chemoradiotherapy and Oxidation Treatment: Adoption of Ultrasound-guided Polymer Nanocarriers - Gu, Xiaowei; Zhu, Dongxiao; Jiang, Yandong; Ma, Yiyi; Yun, Jingting (Cellular and Molecular Biology, 2023)
The research was aimed at discussing the effectiveness of ultrasound-guided polymer nanocarriers in the clinical treatment of tumors by chemoradiotherapy and oxidation treatment. Twenty female Balb/cAnN (BALB/C) mice were selected as the research objects in the experiment. These mice were set up as tumor-bearing mice, and then ultrasound-guided polymers with different doses, including polyethylene glycol-poly 2-bromoethyl methacrylate (PEG-PBEMA) (Micelle group), free small molecules called l-ascorbyl palmitate (PA) (PA group), PA-micelle micellar particles (PA-Micelle group) prepared in the research, and phosphate buffer solution (PBS) (PBS group) were adopted. Besides, the growth of mice was recorded and compared after each operation. Meanwhile, different concentrations of PA-Micelle micellar particles and free small molecules of PA were added to the breast cancer cells of mice, and the concentration changes of glutathione (GSH) were detected to test the oxidation treatment ability of this method. According to the results of the experiment, the tumor volume of mice in the PA-Micelle group prepared in the research was the smallest followed by the PA group, and the tumor volume of mice in the Micelle group was the third smallest. The mice in the PBS group had the largest tumors among mice in all four groups. In oxidation treatment, the GSH concentration of mice in the PA-Micelle group was the lowest, while the GSH concentration of mice in the PA group was almost unchanged. The results of this experiment proved that the therapeutic effect of polymer nanocarriers in tumor chemotherapy and oxidation treatment was more significant than in traditional drug treatment.